Global trends in adolescent peer counseling: a bibliometric analysis (2015-2025) - Elvira La Bula; Titih Huriah (Media Penelitian dan Pengembangan Kesehatan, 2026)
Background: This study presents a comprehensive analysis of the keyword networks, trends, and density of scientific publications discussing peer counseling for adolescents. Peer counseling plays a critical role in addressing adolescent health issues. Publications concerning the role of peer groups within health behavior, health promotion, education, and health services have evolved significantly. However, a comprehensive mapping remains necessary to identify publication trends, collaboration networks, and existing research gaps. Objective: This study aimed to identify research patterns and development trends regarding peer counseling interventions for adolescent health problems, and to uncover largely unexplored areas of research published between 2015 and 2025. Methods: A descriptive and exploratory literature review utilizing a bibliometric approach was employed. Data were retrieved from the Scopus database, and VOSviewer was utilized to visualize keyword relationships, publication trends, and country-level collaborations. Results: Network analysis indicated that the keyword "adolescent" is strongly linked to key topics such as health promotion, health behavior, information processing, school environments, mental health care, and counseling, demonstrating multidimensionality across physical, psychological, social, and educational aspects. Density analysis revealed that adolescent mental health and behavior remain the primary focus. Furthermore, topics such as knowledge mentoring, community-based interventions, and school health services exhibited low density, identifying them as significant research gaps. Conclusion: While existing literature extensively covers mental health and counseling within school and health service frameworks, future research should prioritize community-based interventions, knowledge mentoring, and specialized school health services to address unexplored dimensions of adolescent peer counseling.